A Comparative Study of Clustering Techniques Used in Cloud Computing to Minimize the Adverse Environmental Impact - Raj, Renuka; Vivekanand, Vivekanand; Shukla, Sohit (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is a computing paradigm where various tasks are assigned to a combination of connections, software and services that can be accessed by the user over a network. The research paper aims to reach a theoretical notion of sustainable development with proposing an incentive for reducing global warming through effective clustering techniques and methods. This paper is a comparative study on k-means clustering, map-reduce technique and resource clustering used in cloud computing. The focus of the paper is to suggest better methodology for handling the events of cloud computing and possibly reducing the similar types of events by clustering them. This approach might lead to the reduction of carbon-dioxide gas (which is a greenhouse gas) by less usage of servers in cloud data centers. With the advent of IT services in cloud computing energy consumption it is necessary for the developing technology to progress towards sustainable development rather thrashing and harnessing energy from every possible means.